The Conflicts and Compromises of the Two Cosmologies Making Korean Shamanism - Dongkyu Kim (Religions)
This article explores how the unique cosmology of Korean shamanism, which continues to function as a living religion in contemporary Korea, has been shaped. A key characteristic of the cosmology in Korean shamanism is its combination of two cosmological beliefs. First, it adheres to the general shamanistic cosmology of protection, where suffering caused by supernatural beings can be overcome through the protection of even more powerful beings, who also assist in predicting the future. Second, it incorporates the belief that human life and the universe operate according to specific cosmological principles. The coexistence of these two distinct cosmologies which form an explanatory system of modern Korean shamanism reflects the historical experiences of Koreans with Confucianism during the Joseon dynasty and with Western modernity. In this paper, I analyze the dynamics of conflict and compromise between the two cosmologies through a historical approach and case studies. Specifically, I examine the use of the terms ‘unse (wheel of fortune)’ and ‘spirit’s intervention’ as conceptual metaphors representing each cosmology, as they are employed in interactions between shamans and their clients. Furthermore, I maintain that contemporary Korean shamanism is a form of religious practice constructed as a compromise between various worldviews, including those of shamans and their clients.